2016
DOI: 10.3174/ajnr.a4747
|View full text |Cite
|
Sign up to set email alerts
|

Quiet T1-Weighted Pointwise Encoding Time Reduction with Radial Acquisition for Assessing Myelination in the Pediatric Brain

Abstract: BACKGROUND AND PURPOSE: T1-weighted pointwise encoding time reduction with radial acquisition (PETRA) sequences require limited gradient activity and allow quiet scanning. We aimed to assess the usefulness of PETRA in pediatric brain imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…Recently, Aida et al 13 reported quiet T 1 W sequence for pediatric myelination evaluation. Their quiet T 1 W sequence was 4.8 dB higher than that of ambient sound and the interrater agreement for myelination degree between quiet sequence and conventional T 1 W images were excellent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Aida et al 13 reported quiet T 1 W sequence for pediatric myelination evaluation. Their quiet T 1 W sequence was 4.8 dB higher than that of ambient sound and the interrater agreement for myelination degree between quiet sequence and conventional T 1 W images were excellent.…”
Section: Discussionmentioning
confidence: 99%
“…PETRA keeps the gradient constant for almost the entire repetition and it only slightly changes at the end of each repetition . Accordingly, acoustic noise is only slightly higher compared to the baseline level . Although this effect was not assessed in this study, we believe that the silent scan might have caused less stress for the infants during scanning.…”
Section: Discussionmentioning
confidence: 80%
“…The recently introduced silent MRI technique can dramatically reduce acoustic noise by employing fewer changes in gradient excitation levels. Several reports suggest that silent MRI sequences significantly reduced acoustic noise and provided diagnostic image quality for myelination evaluations in the pediatric brain …”
Section: Techniques To Minimize Sedation For Pediatric Mri Examinationsmentioning
confidence: 99%
“…Several reports suggest that silent MRI sequences significantly reduced acoustic noise and provided diagnostic image quality for myelination evaluations in the pediatric brain. 30,31 Fast Sequences Fast MRI sequences are routinely used on all fetal MRI protocols to overcome various fetal and maternal motion artifacts. These sequences can "freeze" motion and allow for a rapid anatomical survey within 1 minute.…”
Section: Noise Reductionmentioning
confidence: 99%